IMPOLITENESS STRATEGIES OF RON DESANTIS' PRESIDENTIAL ELECTION SPEECH - Firstananda Jenni Yulieta Siagian (LINGUISTIK TERAPAN, 2023)
This comprehensive study embarks on an exploration of incivility strategies manifested in YouTube comments on a political speech by Ron DeSantis, aiming to uncover the intricacies of digital communication and its influence on public discourse. By carefully analysing viewers' comments, this study employs a qualitative methodology to categorise incivility into five different strategies: negative incivility, sarcasm, baldness, positive incivility, and withheld politeness. This classification was crucial in identifying the dominant use of negative incivility, which emerged as the most common strategy among viewers, indicating a direct approach to criticism and disagreement. It was followed by sarcasm and bald on record strategies, which highlighted layered interactions that not only facilitated dissent, but also served to entertain and foster a sense of community among viewers. Although observed less frequently, positive incivility and withheld politeness strategies were also noted, contributing to the diverse spectrum of incivility in digital discourse. The research further delved into the motivations behind the impolite utterances, and revealed that the main drivers were expressing negative feelings towards the utterance or speaker, the desire to entertain, and the intention to advocate for change. In conclusion, this study highlights the complexity of online communication, especially in politically charged contexts, and emphasises the role of digital platforms in shaping public discourse. The study suggests that future research be extended to various digital platforms and cultural contexts to deepen the understanding of online interactions and their evolving nature, thus contributing significantly to the broader discourse on digital incivility and its implications for public dialogue.